2014
DOI: 10.1038/bmt.2014.159
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary exercise testing prior to myeloablative allo-SCT: a feasibility study

Abstract: The feasibility of symptom-limited cardiopulmonary exercise testing (CPET) prior to allo-SCT was assessed in addition to the prognostic value of CPET-derived measures. CPET was performed prospectively on 21 patients with hematologic malignancies, with assessments of peak (for example, peak oxygen consumption, VO2peak) and submaximal (for example, ventilatory threshold (VT)) measures of cardiopulmonary function. No serious adverse events were observed during CPET procedures, with 95% of patients achieving crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 40 publications
2
44
3
Order By: Relevance
“…Finally, it is noteworthy that the observed marked reductions in both functional capacity (as shown in the present study) and exercise capacity [25,26] in HCT patients, as well as the potential clinical importance, creates a strong rationale to test the efficacy of intervention to improve these parameters immediately or closely after HCT. A wealth of studies has provided unequivocal evidence that structured aerobic exercise training is arguably one of the most effective strategies to improve functional and exercise capacity in humans [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is noteworthy that the observed marked reductions in both functional capacity (as shown in the present study) and exercise capacity [25,26] in HCT patients, as well as the potential clinical importance, creates a strong rationale to test the efficacy of intervention to improve these parameters immediately or closely after HCT. A wealth of studies has provided unequivocal evidence that structured aerobic exercise training is arguably one of the most effective strategies to improve functional and exercise capacity in humans [28].…”
Section: Discussionmentioning
confidence: 99%
“…Such metrics can, however, be evaluated by an incremental cardiopulmonary exercise test (CPET) with gas exchange measurement, which provides the reference standard assessment of the peak and submaximal parameters of exercise capacity [17]. In an initial work, we found that pretransplant CPET assessment was not only safe and tolerable but also that both peak and submaximal markers of exercise capacity were significant predictors of OS, pulmonary toxicity, and NRM in 21 patients with hematologic malignancies [25]. Interestingly, 6MWD testing was not a significant predictor of clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…With this as the context, the manuscript in this edition of Bone Marrow Transplantation by Kelsey et al 8 presents interesting data regarding the feasibility and potential usefulness of a pretransplant direct measurement of patient fitness, cardiopulmonary exercise testing (CPET). Performance-based testing such as CPET and 6 min Walk Distance (6MWD) have been studied by the investigators in other cancer settings, such as non-small-cell lung cancer, in which peak oxygen uptake (VO 2 peak) and 6MWD were strong predictors of all-cause mortality.…”
mentioning
confidence: 98%
“…Aerobic exercise has been shown to be safe and effective in preventing loss of physical performance and fatigue in patients undergoing high-dose chemotherapy resulting in significantly less side effects (duration of neutropenia, thrombocytopenia, duration of hospital stay, and severity of diarrhea) [8,53]. Over 80 clinical trials have demonstrated that exercise is a safe and well-tolerated intervention in a range of cancer settings with beneficial effects on quality of life and functional capacity throughout treatment [54].…”
Section: Exercisementioning
confidence: 99%
“…The assessment of functional (exercise) capacity has been recommended for risk stratification of patients having major non-cardiac surgery [7 •• ] and is safe and feasible in cancer patients including those having chemotherapy [8], and the elderly [9]. Cardiopulmonary exercise testing (CPET) may be a logical choice of test for most patients with cancer as it is the most accurate determination of peak oxygen consumption (VO 2 peak) allowing a dynamic evaluation of the cardiovascular and respiratory reserves and allows the differentiation of the mechanism causing limitation [10].…”
Section: Introductionmentioning
confidence: 99%